Molecular markers of prognosis in canine cortisol‐secreting adrenocortical tumours - Sanders, Karin (Vet Comp Oncol, 2019)
Hypercortisolism is caused by a cortisol‐secreting adrenocortical tumour (ACT) in approximately 15%‐20% of cases in dogs. Little is known about which molecular markers are associated with malignant behaviour of canine ACTs. The objective of this study was to identify molecular markers of prognosis, which could be useful to refine prognostic prediction and to identify potential treatment targets. Cortisol‐secreting ACTs were included from 40 dogs, of which follow‐up information was available. The ACTs were classified as low risk of recurrence tumours (LRT; n = 14) or moderate‐high risk of recurrence tumours (MHRT; n = 26), based on the novel histopathological Utrecht score. Normal adrenals (NAs) were included from 11 healthy dogs as reference material. The mRNA expression of 14 candidate genes was analysed in the 40 ACTs and in 11 NAs with quantitative RT‐PCR. The genes' expression levels were statistically compared between NAs, LRTs and MHRTs. Univariate and multivariate analyses were performed to determine the association of the genes' expression levels with survival. Seven genes were differentially expressed between NAs and ACTs, of which pituitary tumour‐transforming gene‐1 (PTTG1) and topoisomerase II alpha (TOP2A) were also differentially expressed between LRTs and MHRTs. In survival analyses, high expression levels of Steroidogenic factor‐1 (SF‐1), PTTG1 and TOP2A were significantly associated with poor survival. In conclusion, we have identified several genes that are part of the molecular signature of malignancy in canine ACTs. These findings can be used to refine prognostic prediction, but also offer insights for future studies on druggable targets.